Unlocking MSME Performance: The Role of Financial Literacy Through Financial Management and Competitive Advantage - Rahma Ulfa Maghfiroh; Riska Agustin (Fakultas Ekonomi, UIN Maliki Malang, 2026)
This research examines how financial literacy can improve MSME performance, with financial management and competitive advantage as mediating variables. Using a quantitative survey of 140 MSMEs in Sidoarjo and SEM-PLS software for analysis, these findings show important and new insights into economic issues. First, MSME performance is not directly impacted by financial literacy. Instead, its impact is fully mediated by competitive advantage and financial management. Second, financial literacy significantly improves financial management practices and strengthens competitive advantage, both of which positively and significantly affect MSME performance. These results demonstrate that financial knowledge alone is insufficient to improve performance unless translated into structured financial practices and strategic differentiation. In real-world conditions, MSMEs that implement systematic bookkeeping, cash flow control, cost efficiency strategies, and product differentiation are more likely to achieve higher profitability and sustainable growth. The study contributes theoretically by extending the Resource-Based View, positioning financial literacy as an internal capability that enhances performance indirectly through managerial and strategic mechanisms. Practically, the findings provide an evidence-based framework for policymakers and MSME practitioners to design targeted financial literacy programs integrated with hands-on financial management training and competitive strategy development.